2008
DOI: 10.21273/hortsci.43.5.1410
|View full text |Cite
|
Sign up to set email alerts
|

Planting Method, Plastic Mulch, and Fumigation Influence Growth, Yield, and Root Structure of Watermelon

Abstract: A 2-year field study was conducted to determine the influence of planting method, i.e., transplanting or direct seeding, black plastic mulch, and soil fumigation on the vine growth, yield, and root structure of diploid hybrid watermelon. The experiment was a split-plot design with fumigation as the main plot and there were four replications. Methyl bromide (337 L·ha−1) was applied to the soil, which was then tarped. Black plastic mulch, 0.61 m wide × 2 mil (Visqueen 4020™) was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Early studies on root development in transplanted and direct-seeded watermelon by Elmstrom (1973) showed that plants grown in small cells did not develop dominant taproots and produced plants with less-developed root systems compared to those that were direct seeded. Similar results were observed by Egel et al (2008) and Martyn (2007Martyn ( , 2008.…”
Section: Cultural Practices That May Reduce Diseasesupporting
confidence: 89%
See 1 more Smart Citation
“…Early studies on root development in transplanted and direct-seeded watermelon by Elmstrom (1973) showed that plants grown in small cells did not develop dominant taproots and produced plants with less-developed root systems compared to those that were direct seeded. Similar results were observed by Egel et al (2008) and Martyn (2007Martyn ( , 2008.…”
Section: Cultural Practices That May Reduce Diseasesupporting
confidence: 89%
“…However, this likely is an artifact of the system, since the transplants were set out at the same time as direct seeding and were already five weeks old (Olson et al 1994). When watermelon transplants were started in the greenhouse at the same time as those direct seeded in the field and then transplanted to the field, direct-seeded plants produced the greatest yields and had better-developed root systems, including a dominant taproot (Egel et al 2008). Early studies on root development in transplanted and direct-seeded watermelon by Elmstrom (1973) showed that plants grown in small cells did not develop dominant taproots and produced plants with less-developed root systems compared to those that were direct seeded.…”
Section: Cultural Practices That May Reduce Diseasementioning
confidence: 99%
“…The optimum environmental temperature for effective watermelon plant growth varies from 18 to 35°C, where any temperature outside this range will slow down growth, maturation, and reduce crop yield (Korkmaz & Dufault, 2001). Transplanting of watermelon seedlings in temperate regions is often delayed to mid to late spring (April to mid‐May) when temperatures are warmer with minimal risks of plant death from low temperatures (Boyhan et al., 2000; Egel et al., 2008; NeSmith, 1999). In the United States, maximum consumption and premium prices for watermelon fruits occurs from June to mid‐July (Kaiser, 2012; https://www.ers.usda.gov/).…”
Section: Introductionmentioning
confidence: 99%